Finite Element Analysis of Layer Non-Uniformity in Polymer Coextrusion Flows - Riquelme, Torres Agustin (My University, 1995)
Coextrusion is an important polymer processing technology that consists of combining layers of different materials in their molten state to form a uniform structure. The final product has the combined properties of the individual components at a cost that is a fraction of lamination. Two basic problems have been defined in polymer coextrusion: the temporal instability of the polymer/polymer interface, and the problem of maintaining a uniform layer and thickness distribution across the die in steady state operation. This work is concerned with the latter problem class. Layer non-uniformity is a distortion of the internal interface that can be seen as a migration or displacement of the more viscous fluid by the less viscous one.
A three-dimensional finite element code was developed to study fundamental issues in the layer non-uniformity problem. One area of study is the contact line region (where the fluid/fluid interface meets the wall). Use of the classical no-slip condition leads to a mathematical singularity. In the past, this was circumvented by extrapolation methods. In this work, a localized slip model allowed a detailed study of the interface behavior near the wall. Also, a rigid (or "stick") contact line was used to explain certain experimentally observed interface shapes.
Based on experimental evidence, two distinct interface deformation mechanisms are proposed: Type I shows a displacement of the more viscous fluid by the less viscous one, with a slippage of the contact line. In Type II, there is an intrusion of the less viscous fluid into the more viscous fluid. Type I and II deformations can be captured using the 3-D thermal model formulation described in this work, but the shape depends on the interplay between the material and die parameters. The value of the slip coefficient at the contact line is important and may be a fundamental characteristic of the particular polymer melt I polymer melt I die material system.
A detailed study of the effect of thermal and geometrical parameters on the final interface shape was conducted. It was found that the thermal dependence of viscosity plays the most important role in determining the final interface shape as compared against other material parameters. The effect of this parameter is more pronounced near the die walls, where the viscous dissipation is higher. The code shows excellent agreement with experimental data for polycarbonate/polycarbonate extrusion systems.
An alternative analysis for the three-dimensional flow of viscoelastic flow in ducts was presented as an attempt to explain experimentally observed complicated interface shapes that cannot be captured by a Generalized Newtonian Fluid model. A modified Phan-Thien Tanner model and a second-order model are used in conjunction with a space-marching finite element code based on the Parabolized Navier-Stokes equations to study the secondary flows in channels.
Keywords: Chemical Engineering; Chemical Engineering